The end of morality taking moral abolitionism seriously - Garner, Richard 1936-; Joyce, Richard (Routledge, 2019)
According to the moral error theorist, all moral judgments are mistaken. The world just doesn't contain the properties and relations necessary for these judgments to be true. But what should we actually do if we decided that we are in this radical and unsettling predicament-that morality is just a widespread and heartfelt illusion? One suggestion is to eliminate all talk and thought of morality (abolitionism). Another is to carry on believing it anyway (conservationism). And yet another is to treat morality as a kind of convenient fiction (fictionalism). We tend to think of moral thinking as valuable and useful (e.g., for motivating cooperative behavior), but we can also recognize that it can be harmful (e.g., hindering compromise) and even disastrous (e.g., inspiring support for militaristic propaganda). Would we be better off or worse off if we stopped basing decisions on moral considerations?This is a collection of twelve brand new chapters focused on a critical examination of the options available to the moral error theorist. After a general introduction outlining the topic, explaining key terminology, and offering suggestions for further reading, the chapters address questions like: Is it true that the more that people are motivated by moral concerns, the more likely it is that society will be elitist, authoritarian, and dishonest? Is an appeal to moral values a useful tool for helping resolve conflicts, or does it actually exacerbate conflicts? Would it even be possible to abolish morality from our thinking? If we were to accept a moral error theory, would it be feasible to carry on believing in morality in everyday contexts?